Achieving Universal Primary Education by 2015 : A Chance for Every Child - Bruns, Barbara; Mingat, Alain; Rakotomalala, Ramahatra (Washington, DC: World Bank, 2013)
A number of countries committed themselves to the Millennium Development Goals (MDGs), aimed at eradicating extreme poverty, and improving the welfare of people by the year 2015. The book assesses whether universal primary education can be achieved by 2015. The study focuses on the largest low-income countries that are furthest from the goal, home to about seventy five percent of the children out of school globally. By analyzing education policies, and financing patterns in relatively high-performing countries, the study identifies a new policy, and financing framework for faster global progress in primary education. The authors use a simulation model to show how adoption of this framework, could accelerate progress in low-income countries, currently at risk of not reaching the education MDG. The study however, makes it clear that worldwide attainment of universal primary education by 2015, will necessitate an even stronger combination of political will, deep and sustained reform, faster dissemination of best practices, and intensified financial effort than has been marshaled to date.